A case of lichen planus pemphigoides with autoantibodies to the NC16a and C‐terminal domains of BP180 and to desmoglein‐1. (1st November 2014) - Sekiya, A.; Kodera, M.; Yamaoka, T.; Iwata, Y.; Usuda, T.; Ohzono, A.; Yasukochi, A.; Koga, H.; Ishii, N.; Hashimoto, T.
Summary: Lichen planus pemphigoides (LPP) is a rare autoimmune blistering disease that occurs in association with lichen planus (LP). This report describes a 59‐year‐old Japanese female patient with LPP. The patient first showed LP lesions on her hands, and subsequently developed bullae on her extremities and erosions of the oral mucosa. The patient's serum was positive for IgG autoantibodies against the BP180 NC16a domain, the BP180 C‐terminal domain and desmoglein‐1. However, a serum sampled one and a half years before the diagnosis of LPP was negative for autoantibodies against BP180 NC16a and BP180 C‐terminal domains. These findings strongly suggest that the damage to the basal cells in the LP lesions exposed a sequestered antigen or formed neoantigens, leading to the production of pathogenic autoantibodies for LPP. Most of the previous cases of LPP have produced autoantibodies to the NC16a domain of BP180. This is the first case in which autoantibodies to the C‐terminal domain of BP180 were detected. The oral mucosal symptoms in this case may have been caused by autoantibodies to the BP180 C‐terminal domain.